Mu-opioids activate phospholipase C in SH-SY5Y human neuroblastoma cells via calcium-channel opening. - Smart, D (1995)
We have recently reported that, in SH-SY5Y cells, mu-opioid receptor occupancy activates phospholipase C via a pertussis toxin-sensitive G-protein. In the present study we have further characterized the mechanisms involved in this process. Fentanyl (0.1 microM) caused a monophasic increase in inositol 1,4,5-trisphosphate mass formation, with a peak (20.5 +/- 3.6 pmol/mg of protein) at 15 s. Incubation in Ca(2+)-free buffer abolished this response, while Ca2+ replacement 1 min later restored the stimulation of inositol 1,4,5-trisphosphate formation (20.1 +/- 0.6 pmol/mg of protein). In addition, nifedipine (1 nM-0.1 mM), an L-type Ca(2+)-channel antagonist, caused a dose-dependent inhibition of inositol 1,4,5-trisphosphate formation, with an IC50 of 60.3 +/- 1.1 nM. Elevation of endogenous beta/gamma subunits by selective activation of delta-opioid and alpha 2 adrenoceptors failed to stimulate phospholipase C. Fentanyl also caused a dose-dependent (EC50 of 16.2 +/- 1.0 nM), additive enhancement of carbachol-induced inositol 1,4,5-trisphosphate formation. In summary, we have demonstrated that in SH-SY5Y cells activation of the mu-opioid receptor allows Ca2+ influx to activate phospholipase C. However, the possible role of this mechanism in the process of analgesia remains to be elucidated.